2023
DOI: 10.1021/acs.biomac.2c01203
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Recognition of Phosphodiester-Based Donor and Acceptor Oligomers Forming Gels in Water

Abstract: Inspired by automated DNA synthesis, electron-rich dialkoxynaphthalene (DAN) donor and electron-deficient naphthalene-tetracarboxylic diimide (NDI) acceptor phosphodiester-linked homohexamers were synthesized by the phosphoramidite method. Two types of hexamers were prepared, one with only one phosphodiester between the aromatics (i.e., DAN or NDI) and a second with two phosphodiesters around a propanediol between the aromatics, leading to the latter more flexible and more hydrophilic hexamers. The folding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…In another study, we showed that in crystals of the aptamer:thrombin complex, NDI and DAN form an alternate stacking starting from an NDI close to the DNA . These data confirmed molecular modeling studies that predicted alternate stacking. , …”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In another study, we showed that in crystals of the aptamer:thrombin complex, NDI and DAN form an alternate stacking starting from an NDI close to the DNA . These data confirmed molecular modeling studies that predicted alternate stacking. , …”
Section: Introductionsupporting
confidence: 75%
“…Along with our previous works devoted to the synthesis of DAN-NDI-based supramolecular structures as an alternated sequence, or as a duplex formed by recognition of a hexaDAN and a hexaNDI, these results prompted us to investigate in depth the influence of DAN:NDI pairs as surrogate base pairs in DNA duplexes. We present here a comprehensive study, performed by thermal denaturation, of the effect of charge-transfer interactions induced by the incorporation of multiple DAN (D) and NDI (N) units into DNA duplexes and hairpins at different positions.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…42 Similar acceptor-donor recognition in phosphodiester oligomers has been shown to assemble hydrogel networks. 43 The Häner group reported multiple studies on the self-assembly of DNA amphiphiles based on pyrene, 44 phenanthrene 45 or tetraphenylethylene moieties 46 with minimal variation of the monomer sequences. A systematic investigation of the influence of the sequence of block oligo ( phosphodiester)s, therefore, remains lacking.…”
Section: Introductionmentioning
confidence: 99%